Hubungan Ketepatan Penggunaan Antibiotik dengan Lama Rawat dan Luaran pada Pasien Infeksi Saluran Pernapasan - Anisa Lintang; Nadyah Haruna; Darmawansyih; Asrul Abdul Azis; Takdir (Universitas Islam Negeri Alauddin Makassar, 2025)
Respiratory tract infections occur when germs or bacteria enter the respiratory tract and reproduce, developing symptoms. A significant proportion, around 40-60%, of patients with respiratory tract infections need antibiotic therapy due to the presence of viral and bacterial infections. Antibiotic resistance escalates the expenses of medical care, prolongs the duration of hospitalisation, and can elevate the likelihood of death. This study aims to establish the correlation between the utilisation of antibiotics and the duration of hospitalisation and outcomes in patients diagnosed with respiratory tract infections at the Makassar Hajj Hospital from 2021 to 2023. This study employs a quantitative approach and utilises a cross-sectional research methodology. The research sample consisted of 99 respondents diagnosed with respiratory tract infections. The data from their medical records were collected using the purposive sampling technique. The chi-square analysis of the data revealed a significant association between the length of stay and outcomes, with a p-value of less than 0.001. The data indicate a correlation between the use of antibiotics and the duration of hospitalisation and outcomes in patients with respiratory tract infections at the Makassar Hajj Hospital from 2021 to 2023.